Cat allergen exposure in a naturalistic exposure chamber: A prospective observational study in cat‐allergic subjects. Issue 2 (14th January 2022) - Yang, William H.; Kelly, Suzanne; Haya, Laura; Mehri, Rym; Ramesh, Divya; DeVeaux, Michelle; Wang, Claire Q.; Meier, Pretty; Narula, Sumit; Shawki, Furat; Pennington, Ryan; Perlee, Lorah; et al.
Abstract: Background: To determine the proportion and reproducibility of cat‐allergic mild asthmatics with early asthmatic response (EAR) during cat allergen exposure in a naturalistic exposure chamber (NEC). Methods: This was a prospective, observational study in 30 cat‐allergic mild asthmatics who received two 180‐min cat‐allergen ( Felis domesticus allergen 1 [Fel d 1]) challenges 27 days apart in an NEC. Results: An EAR (≥20% reduction from baseline in forced expiratory volume in 1 s [FEV1]) was observed in 67% and 52% of subjects at first and second NEC exposure, respectively, with similar median time to EAR; 44% of subjects had an EAR on days 1 and 28. Late asthmatic response (≥15% reduction in FEV1 within 24 h of NEC exit) was observed in 33% of subjects following either exposure. Average FEV1 and total nasal symptom score during NEC exposure were highly correlated within subjects between NEC exposures ( r = 0.91, p < 0.0001; r = 0.73, p < 0.001), but total ocular symptom score was not. Time to EAR, but not average FEV1, was significantly associated with NEC Fel d 1 concentration, which was variable. There were no serious adverse events; 12/30 subjects experienced 20 adverse events (including asthma, 10%; headache, 10%). Conclusions: The NEC model demonstrates that average FEV1 change is highly reproducible and has a low correlation with cat allergen levels. However, time to EAR and incidence of EAR are less reproducible and are highly correlated with NEC allergen levels. Average FEV1, rather than incidence of EAR or time to EAR, could be considered as an endpoint for interventional trials testing cat‐specific anti‐allergy therapies using an NEC. Abstract : In this prospective, observational study in cat‐allergic mild asthmatics who received cat‐allergen challenges in an NEC, 67% and 52% of subjects experienced an EAR at first and second exposure. The time to and incidence of EAR were highly correlated with NEC allergen levels, while average FEV1 during NEC challenges was highly correlated within subjects between NEC exposures. Average FEV1 could be a possible endpoint for interventional trials testing cat‐specific anti‐allergy therapies using an NEC.